2020
DOI: 10.1128/jcm.01103-20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MALDI Biotyper Interpretation Criteria for Accurate Identification of Nontuberculous Mycobacteria

Abstract: Mycobacteria identification by MALDI-TOF MS requires not only a good protein extraction protocol but also an adequate cut-off score in order to provide reliable results. The aim of this study was to assess the cut-off scores proposed by the MALDI-TOF MS system for mycobacteria identification. A total of 693 clinical isolates from liquid media and 760 from solid media were analysed, encompassing 67 different nontuberculous mycobacteria (NTM) species. MALDI-TOF MS identified 558 (80.5%) isolates from liquid medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 28 publications
(30 reference statements)
0
35
0
Order By: Relevance
“…Mycobacterial misidentifications by MALDI-TOF MS have been reported in literature, even with high log(score) 20 . Fortunately, this is not a common phenomenon.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mycobacterial misidentifications by MALDI-TOF MS have been reported in literature, even with high log(score) 20 . Fortunately, this is not a common phenomenon.…”
Section: Discussionmentioning
confidence: 98%
“…In summary, MALDI-TOF MS demonstrated an extraordinary inter-laboratory reliability for the identification of NTMs, reaching a high concordance among identifications obtained in participating centres. Besides, sonication of the bacterial pellet has shown to be a good alternative to the MycoEX procedure 20 . Misidentifications were scarce and they were considered as minor errors since the identifications provided by the MALDI-TOF MS corresponded to species from the same complex.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the rapid detection and identification of NTM species is very important for the diagnosis and treatment of NMLD. At present, most of the reported NTM strain identification methods are based on cultures to obtain isolates before strain identification (10)(11)(12). Due to the long cultivation time of mycobacteria, it takes 1-8 weeks and sometimes as long as 12 weeks to obtain a culture (13).…”
Section: Discussionmentioning
confidence: 99%
“…For the Bruker systems, MALDI-TOF scores higher or equal to 2.0 are required for a high confidence identification. Nevertheless, due to the biological features of mycobacteria, previous studies have shown that lower scores can effectively be used for NTM identification (15,26). Therefore, MALDI-TOF scores higher or equal to 1.8 were considered high confidence identifications as described elsewhere (26) and were used to establish a positive NTM identification.…”
Section: Protein Extraction and Maldi-tof Ms Analysismentioning
confidence: 99%
“…However, due to the increased costs and technical and training requirements of WGS, its implementation in routine diagnosis of NTM is limited. As a result, many laboratories still use a combination of probes and Sanger sequencing as a reference method to identify NTM species (8,15,16).…”
Section: Introductionmentioning
confidence: 99%